Development and validation of a multiclass method for the determination of antibiotic residues in honey using liquid chromatography-tandem mass spectrometry. Issue 4 (3rd April 2017) - El Hawari, Khaled; Mokh, Samia; Doumyati, Samah; Al Iskandarani, Mohamad; Verdon, Eric
ABSTRACT: A new, simple and fast method was developed for the determination of multi-class antibiotic residues in honey (sulfonamides, tetracyclines, macrolides, lincosamides and aminoglycosides). Separation and determination were carried out by LC-MS/MS. During sample preparation, various parameters affecting extraction efficiency were examined, including the type of solvent, pH, efficiencies of cleavage of N-glycosidic linkages by hydrochloric acid, ultrasonic extraction and its duration compared with shaking, along with dispersive SPE clean-up. Experiments with fortified samples demonstrated that 10 min of ultrasonic treatment with acidified methanol (HCl 2 M) followed by dispersive SPE clean-up with 50 mg PSA gave an effective sample preparation method for several classes of antibiotics in honey. Anhydroerythromycin A, erythromycin A enol ether and desmycosin were used as markers for the presence of erythromycin A and tylosin A in honey samples. The method was validated according to European Commission Decision (EC) No. 2002/657. The recoveries of analytes ranged from 85% to 111%. Repeatability and intra-laboratory reproducibility were < 20.6% and 26.8%, respectively. Decision limit (CCα) and detection capability (CCβ) ranged from 6 to 9 µg kg – 1 and from 7 to 13 µg kg – 1, respectively, except for streptomycin and neomycin, which showed slightly higher CCα at 25 µg kg – 1 and CCβ at 34 µg kg – 1 . Finally, the method was applied to the honey test material 02270 through a FAPAS proficiency test (PT) for the determination of tetracyclines. PT results were obtained within a z -score range of ±2, proving that the validated method is suitable for routine analysis to ensure the quality of honey. GRAPHICAL ABSTRACT: